ANALISIS EFISIENSI TEKNIS ALOKASI INPUT USAHA TANI PADI SAWAH DI DAERAH IMPENSO WILAYAH TAMAN NASIONAL LORE LINDU (TNLL) PROVINSI SULAWESI TENGAH - Arifuddin Lamusa (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The objectives of the research were to examine whether there were differences in the technical efficiency of input allocation of rice farming between wt (with-enso) and wo (without-enso) areas at various planting season and to study whether the input allocation was technically efficient. Data analysis used a production function analysis method and dummy variables. The research results showed that: the dummy variables were significant in planting season II but not significant in planting season I.   The technical efficiency of input allocation in wt and wo areas was significant at planting season I and II, whereas at planting season–t the efficiency was not significant.  The efficiency of urea, SP36 and KCl fertilizer allocation in wt and wo areas was significant at all planting seasons while that of ponska fertilizer only at planting season I and II the efficiency was significant. On the contrary, the efficiency of pesticide in both areas was only significant at planting season-t.